(3GdMO ef VZhW GdYeds - (3OhQdfZ cfOQSdjs; (3ecJHI dHfGf fGTQhfs ((3HjQhJs (3ecJHI dHfGf fGTQhfs, 2001)
(3jbOe gPG GdcJGH CSGdjH YdejI JhVM dc cjajI JMdjd hJMSjf CfeGW GdYed GdeQgb, hcjajI JUfja GdChdhjGJ, hcjajI JaIjV GdYed Edi ef jfhH Yfg hcjajI EjLGO GdhbJ GdcGaj ddGSJQNGA(B. (3jbhe GdfU GdhGVM hGdQShe GdJhVjMjI HJZWjI cGaI LhGfH GdJYGed eY GdJhJQ hVZhW GdYed(B. (3Jecfc GdbhGFe GdHSjWI GdNGUI HGdeQGLYI ef GdEYOGO GdJGe dGSJQGJjLjI NGUI HGdMO ef VZhW GdYed(B. (3Jbhe GdCTWGd GdJhVjMjI GdSgdI Gdage HYQV eNJda GdHOGFd GdNGUI HGdCOGA ceG JhaQ dc gPg GdCTcGd CeKdI YXjeI GdaGFOIs
(3jhQc HQSs
(3GdfU JQLe Gdi GdYQHjI ef GddZI GdGfLdjRjIs
elwadi
1 7 13 21
Keywords: (3EOGQI GdCYeGds; (3GdEOGQI GdJfajPjIs